PENERAPAN METODE FILTER GAUSSIAN DALAM PERBAIKAN KUALITAS CITRA SATELIT MODIS - Tri Handayani; Erna Alimudin (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
One technology that uses satellite capabilities that can capture the image of an area is the MODIS (Moderate Resolution Imaging Spectroradiometer) sensor, the resulting image may experience noise (noise) this is caused when sending through the transmission line, the image is too dark or bright, the image less sharp or blurred. For that we need a method of noise reduction such as remote sensing through satellite imagery. The purpose of this study is to apply the Gaussian lowpass filter method in improving the quality of fashionable satellite imagery in order to have good image quality. The results of PSNR show the highest value on the MOD_04 image, with smoother image results, the resulting PSNR value is 19.7791 higher than other images, where the higher the PSNR value, the better the resulting image.